Cobalt addition effects on martensitic transformation and microstructural properties of high-temperature Cu-Al-Fe shape-memory alloys - Yildiz, Koksal; Kok, Mediha; Dagdelen, Fethi (Springer, 2015)
The effects of the addition of Co on the martensitic transformation and microstructural properties of high-temperature Cu-Al-Fe shape-memory alloy systems were studied by means of DSC, XRD, optical microscopy and Vickers microhardness measurements. DSC analyses indicated that the Cu-Al-Fe alloy displayed high-temperature shape-memory characteristics and that the Co additions dramatically influenced the martensitic transformation of the alloys. Structural and morphological investigations showed that the alloys had 18R martensite structure and contained different precipitates. With increasing amounts of Co, it was seen that elemental compositions of precipitates changed and their volume fractions increased and, therefore, both thermal stability and microhardness values of the alloys were affected. As a result, whereas microhardness values of the alloys were increased by 313 +/- A 7.76 to 365.75 +/- A 7.84 Hv, the alloys exhibited poor thermal stability and high volume fraction of precipitates following Co addition.
Keywords: Cu-Al-Fe; High-temperature martensite; DSC; Microhardness